Limiting fusion levels by combining anterior cervical decompression and fusion with posterior laminectomy: Technical note - Chin, Kingsley R. (J Orthop, 2018)
BACKGROUND: Authors aim to report on the outcomes of combining selective anterior cervical decompression and fusion (ACDF) with laminectomy in patients with cervical spondylotic radiculomyelopathy (CSR). METHODS: 10 patients with ACDF and posterior laminectomy reviewed. RESULTS: 60% female population, mean age 61 ± 3 years, mean BMI 24.7 ± 3.4 kg/m(2). VAS and NDI showed significant improvement, p < 0.001, p = 0.02 respectively. Mean PCS 31.9 ± 2.7, MCS 38.9 ± 3.4 improved to mean PCS 42.2 ± 5.1, MCS 51.0 ± 4.7, p = 0.09 and 0.06 respectively. At final follow up fusion rate was 90% and all patients had Nurick Grade 0. CONCLUSION: In this pilot study, procedure shown to be safe with improved symptoms.